The Effectiveness of Gestalt Counseling in Increasing Students' Self-Confidence - Robbi Asri; Herman Nirwana; Mudjiran; Yeni Karneli; Rendy Amora (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the effectiveness of gestalt counseling in increasing students' self-confidence, where we know that currently students have low self-confidence, such as students who are afraid to come forward to answer questions because their classmates like to make fun of students' writing, making students afraid to express their opinions and ask. Everyone actually has problems with this term. There are people who feel they have lost self-confidence in almost all areas of their life. Maybe it's related to self-crisis, depression, loss of control, feeling helpless to look at the bright side of the future, and so on. There are also people who feel they are not yet confident/confident in what they are doing or what they are pursuing. There are also people who feel less confident when facing certain situations or circumstances. These problems that occur need to be resolved so that they do not interfere with daily life. This article also discusses Gestalt counseling as a strategy for increasing students' self-confidence. The method used is a literature review with critical analysis of research being conducted on a specific topic.